REFLEKSI EPISTIMOLOGI DALAM METODOLOGI PENELITIAN (Suatu Kontemplasi atas Pekerjaan Penelitian) - Saifullah Saifullah (De Jure: Jurnal Hukum dan Syari'ah, 2013)
Research methodology is the application of epistemology in philosophical which is realized by logico hypotetico verificative-deducto hypothetico verificative. The results of the evaluation of the quality of the research methodology that gave rise buildings recently become a standard formula valid and tested public. In this context it is necessary scrutiny of the functioning and the importance of pre usability, and value the benefits of the research process so that the quality of research produced a positive impact on building science researchers. The role of the researcher holds a central position of being able to adjust the ground circumstances. Benefit value for the benefit of life as the goal of research in theory and practical should be explicitly and implicitly always accompanies every step of research. A consequence of the value of the benefits of scientific research which is undertaken is delivering research results to the user community. The use of research methodologies in the study strongly influenced the extent of the ability of researchers and scientists at the clump science community are able to map the identity of the building a distinctive methodology of scientific disciplines that is useful for subsequent research. Metodologi Penelitian merupakan penerapan epistimologi secara filsafati yang diwujudkan dengan logico  hypotetico  verificative-deducto  hypothetico  verificative.  Hasil  evaluasi terhadap  kualitas  bangunan  metodologi  penelitian  yang  memunculkan  formula  baru menjadi standar yang valid dan teruji publik. Dalam konteks ini maka perlu pencermatan tentang fungsi dan kegunaan akan pentingnya pra, proses dan nilai manfaat riset agar kualitas riset yang dihasilkan berdampak positif pada bangunan keilmuan peneliti. Peran peneliti  memegang  posisi  sentral  karena  mampu  menyesuaikan  situasi  dan  kondisi lapangan. Nilai kemanfaatan bagi kemaslahatan hidup sebagai tujuan riset secara teoritis dan praktis sebaiknya secara eksplisit dan implisit selalu menyertai setiap langkah riset. Konsekuensi ilmiah dalam nilai manfaat riset yang dilakukan adalah menyampaikan hasilhasil riset ke masyarakat pengguna. Penggunaan metodologi penelitian dalam riset sangat dipengaruhi sejauhmana kemampuan peneliti dan komunitas ilmuan pada rumpun ilmu mampu memetakan jati diri bangunan metodologi disiplin keilmuan yang khas sehingga bermanfaat bagi peneliti berikutnya.